Transformative Constitutionalism in Africa Fledgling Democracy - Mendy, Ousu (Constitutional Law Review, 2025)
This study critically examines constitutionalism in Africa, addressing challenges posed by fragile democratic institutions and the imperative for transformative constitutionalism. Although democratic legitimacy relies on legality and popular sovereignty, transformative constitutionalism demands proactive efforts beyond legal formalism to drive social change. Employing normative legal analysis of secondary data, the research reveals that legal pluralism and entrenched constitutional principles significantly impede transformative progress in post-colonial African states. The study highlights the necessity of adopting transformative constitutionalism to reinforce democratic resilience and establish coherent legal and political frameworks tailored to Africa distinct socio-political realities.